The discourse of attire and adornment of the dead and their mourners in Muslim medieval legal texts - Hirsch, Hadas (The journal of religion & society, 2012)
The article examines the legal discussion of attire and adornment of the dead and their mourners in early Islam, as death rituals often provide insight into cultures and their relationship with both the dead and the living. The role of fiqh (jurisprudence) and fatawa (formal legal opinion) collections was to accommodate the often abstract law to the community's needs. Together with the frequently hypothetical theoretical discussion, they reflect the community's practices, since the written texts dealt with reality in their determination of what was and was not permitted according to legal norms. Medieval Muslim legal discussion of the attire and adornment worn by men and women during burial and mourning was aimed at establishing and preserving the patriarchal gender-based hierarchy. The fact that some prohibitions regarding the outward appearance of the two sexes apply only to the living reflects the decrease in the power of gender differentiation at the end of the human existence cycle. For the relatives of the deceased, the mourning period is a transition stage characterized by special markers of clothing and adornment. During the three days of mourning, mourners of both sexes are forbidden to change their clothes, to wear jewelry, or to use scent. However, in all other matters of attire and adornment gender differentiation does exist, since only widows have to continue wearing the outer signs of mourning. They are forbidden to wear colored clothing or use perfume, henna and cosmetics for a period of four months and ten days.